PENGGUNAAN ABU KULIT BATANG SAGU SEBAGAI BAHAN TAMBAH CAMPURAN AC-WC - Ahmad, Nurmiati (Jurusan Teknik Sipil, 2025)
The surface layer of road pavement construction is the layer that receives the most load; therefore, the material that makes up this layer must be a material that is strong enough. The type of surface layer of road pavement construction commonly used consists of various types, one of which is AC-WC, because it has high flexibility and is resistant to plastic melt. Sago is one of the most important sources of carbohydrates in Ambon City, including in Wakasihu, where residents consume sago as a staple food other than rice. For the people of Wakasihu, sago is a food that is still consumed by the community. Based on the results of Marshall's testing on the use of sago bark ash as an added ingredient in the AC-WC mixture, it can be concluded that the sago ash used from 0%, 2.5%, 5.% asphalt content meets the requirements. However, for VIM and VMA, they do not meet VFB requirements; stability and Flow MQ meet requirements. So that the sago ash content that can be used as an asphalt additive in asphalt mixing is 2.5% and 5.% sago ash content. From the results carried out, the sago ash content that can be used is 0%, 2.5% and 5.%, but the sago ash content whose values are best to be used as the most optimal mixture is a mixture with a sago ash content of 2.5%.